Analisis Yuridis Tuntutan Jaksa untuk Menuntut Hukuman Mati dalam Tindak Pidana Korupsi (Studi Putusan Nomor 50/Pid.Sus-TPK/2021/PN Jkt.Pst) - Moh Romli (Sultan Jurisprudence: Jurnal Riset Ilmu Hukum, 2022)
Corruption is an extraordinary crime (extraordinary crime), so how to handle it must also be done in extraordinary ways as well. Regarding the issue of corruption that the author raises, namely the case of corruption committed by Heru Hidayat, President Commissioner of PT Trada Alam Minera Tbk, corruption at PT Asabri is also called the mega-corruption case because the value of state losses is fantastic, reaching Rp. 22.7 trillion. This type of research is a normative juridical research, which examines laws and regulations, theories, or the opinions of legal experts. Regulations related to prosecuting the death penalty are contained in the Guidelines for the Attorney General of the Republic of Indonesia Number 1 of 2019 concerning Criminal Prosecutions for Criminal Acts of Corruption and Article 2 Paragraph (2) of Law Number 30 of 1999 concerning Eradication of Criminal Acts of Corruption as amended in Law Number 20 of 2001 concerning Eradication Corruption Crimes.